2012
DOI: 10.1007/s11433-011-4601-9
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of shock wave buffet and its suppression on an OAT15A supercritical airfoil by IDDES

Abstract: In the present paper, extremely unsteady shock wave buffet induced by strong shock wave/boundary-layer interactions (SWBLI) on the upper surface of an OAT15A supercritical airfoil at Mach number of 0.73 and angle of attack of 3.5 degrees is first numerically simulated by IDDES, one of the most advanced RANS/LES hybrid methods. The results imply that conventional URANS methods are unable to effectively predict the buffet phenomenon on the wing surface; IDDES, which involves more flow physics, predicted buffet p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(20 citation statements)
references
References 39 publications
3
17
0
Order By: Relevance
“…Secondly, the unsteadiness captured in Fig. 5a is not harmonic as previously seen for the RBC12 aircraft [19] or in 2D studies for the OAT15A aerofoil [9][10][11][12][13][14][15][16]. Although not shown here, the drag coefficient, C D , and pitching moment coefficient, C M , exhibit similar patterns.…”
Section: Global Forces and Surface Samplingsupporting
confidence: 61%
See 1 more Smart Citation
“…Secondly, the unsteadiness captured in Fig. 5a is not harmonic as previously seen for the RBC12 aircraft [19] or in 2D studies for the OAT15A aerofoil [9][10][11][12][13][14][15][16]. Although not shown here, the drag coefficient, C D , and pitching moment coefficient, C M , exhibit similar patterns.…”
Section: Global Forces and Surface Samplingsupporting
confidence: 61%
“…With advancing technology, the use of Computational Fluid Dynamics (CFD) in shock-buffet prediction has increased substantially in the last two decades. The 2D experimental results for the OAT15A aerofoil [8] have been used for validation in a series of CFD studies in which the Unsteady Reynolds-averagedNavier-Stokes (URANS), Large Eddy Simulations (LES), and hybrid RANS-LES approaches have been applied [9][10][11][12][13][14][15][16]. The variation in results presented revealed that there is still an uncertainty in prediction of shock-buffet by means of URANS, particularly when closed with eddyviscosity-based turbulence models.…”
mentioning
confidence: 99%
“…It is mainly developed to resolve the unsteady flows accurately, and has been applied in the incompressible [25,26] and transonic turbulent flows [27] successfully. To simulate the hypersonic RIT, the inviscid fluxes are solved using typical Roe Riemann solver, through 4th order MDCD-WENO reconstruction for the original variables.…”
Section: Methodsmentioning
confidence: 99%
“…To save time and energy, high-speed flights are usually done by modern, large commercial aircraft, which always cruise between Mach 0.7 and 0.9 by employing supercritical wings [1][2][3]. These Mach numbers fall in the typical transonic flow range; consequently, unsteady shockwave/boundary layer interactions could induce intensive, large-scale, unsteady lift, and transonic buffet will be the result [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that by introducing streamwise vortices, streamwise slot control may help delay or prevent downstream separation. By solving Navier-Stokes equations enclosed by an IDDES turbulence model, Huang et al [1] investigated the influence of vortex generators with inclined angles on the transonic buffet of an OAT15A airfoil. They found that the time-averaged location of the shockwave was pushed downstream; thus, the root-mean-square of the oscillating force in the buffeting zone decreases, and the total lift is enhanced.…”
Section: Introductionmentioning
confidence: 99%